Thermoelectric La-doped SrTiO3 epitaxial layers with single-crystal quality: from nano to micrometers. Issue 1 (1st January 2017) - Apreutesei, Mihai; Debord, Régis; Bouras, Mohamed; Regreny, Philippe; Botella, Claude; Benamrouche, Aziz; Carretero-Genevrier, Adrian; Gazquez, Jaume; Grenet, Geneviève; Pailhès, Stéphane; Saint-Girons, Guillaume; Bachelet, Romain
Abstract: High-quality thermoelectric La0.2 Sr0.8 TiO3 (LSTO) films, with thicknesses ranging from 20 nm to 0.7 μm, have been epitaxially grown on SrTiO3 (001) substrates by enhanced solid-source oxide molecular-beam epitaxy. All films are atomically flat (with rms roughness < 0.2 nm), with low mosaicity (<0.1°), and present very low electrical resistivity (<5 × 10 −4 Ω cm at room temperature), one order of magnitude lower than standard commercial Nb-doped SrTiO3 single-crystalline substrate. The conservation of transport properties within this thickness range has been confirmed by thermoelectric measurements where Seebeck coefficients of approximately –60 μV/K have been recorded for all films. These LSTO films can be integrated on Si for non-volatile memory structures or opto-microelectronic devices, functioning as transparent conductors or thermoelectric elements. Abstract :